Identification, morphology, and composition of mantis shrimp crustacean (Stomatopoda) catch in the waters of Bireuen Regency - Irfannur Irfannur; Akmal Izwar; Said Ikram; Muliari Muliari; Yusrizal Akmal; Muhammad Radhi; Agung Setia Batubara (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Bireuen Regency, located on the eastern coast of Aceh, is rich in natural resources, particularly in marine fisheries. Among these, mantis shrimp are a notable resource, though their population dynamics remain undocumented. Currently, mantis shrimp are considered bycatch by local fishermen, with most being discarded. To address this gap, this study aimed to identify and analyze the morphology and composition of mantis shrimp in the waters of Bireuen Regency. The research was conducted from October 2024 in Gandapura District, employing purposive random sampling at three designated sites. The species identified was Harpiosquilla raphidea. Morphological measurements revealed six body segments: head length (PK), head width (LK), body length (PB), body width (LB), tail length (PE), and tail width (LE). Results indicated that mantis shrimp constituted 50% of the catch, followed by tiger shrimp (25%) and kelong shrimp (25%). The length-weight relationship of mantis shrimp showed a b-value of <3, signifying negative allometry, where growth in length outpaces growth in weight. These findings provide baseline data for further studies on mantis shrimp populations and their potential utilization in sustainable fisheries.